2017
DOI: 10.1002/ccd.27416
|View full text |Cite
|
Sign up to set email alerts
|

Caliber and fitness of the axillary artery as a conduit for large‐bore cardiovascular procedures

Abstract: Objectives: We sought to describe the caliber and vascular health of the subclavian and axillary arteries as related to their potential utilization in complex cardiovascular procedures.Background: Patients referred for advanced catheter-based therapies frequently have lower

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…The axillary artery has emergent as a feasible alterative access route for percutaneous large‐bore access in patients with unsuitable iliofemoral arteries. A recent multi‐detector axial tomographic comparative analysis of axillary and iliofemoral arteries in 208 patients revealed that axillary artery was slightly smaller than the common femoral artery (mean minimal luminal diameter = 6.0 ± 1.1 mm and 6.6 ± 1.8 mm, P < 0.01) but was less likely to have a significant stenosis (2% vs 12%, P < 0.01) or moderate to severe calcifications (9% vs 64%, P < 0.01) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The axillary artery has emergent as a feasible alterative access route for percutaneous large‐bore access in patients with unsuitable iliofemoral arteries. A recent multi‐detector axial tomographic comparative analysis of axillary and iliofemoral arteries in 208 patients revealed that axillary artery was slightly smaller than the common femoral artery (mean minimal luminal diameter = 6.0 ± 1.1 mm and 6.6 ± 1.8 mm, P < 0.01) but was less likely to have a significant stenosis (2% vs 12%, P < 0.01) or moderate to severe calcifications (9% vs 64%, P < 0.01) …”
Section: Discussionmentioning
confidence: 99%
“…These alternatives usually require surgical exposure and are often associated with increased morbidity and longer hospitalizations . Percutaneous transaxillary large‐bore access has been recently described as a promising alternative for patients with inadequate femoral access . We provide a step‐by‐step guide for percutaneous axillary access and closure for the insertion of a left ventricular assist device.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is typically smaller than the common femoral artery, the axillary artery has been shown to be an acceptable alternative access site for MCS in the presence of severe PAD . Both the left and right axillary arteries have been used for TAVR, and Impella insertion .…”
Section: Axillary Alternative Access Occlusive Sheathmentioning
confidence: 99%
“…5 mm has also been suggested. 8 Calcified vessels are more prone to dissection or distal embolisation and can lead to challenges deploying closure devices at the time of explant. 10 For this reason, heavy calcification of the AA warrants additional consideration before large-bore access, aided by a detailed ultrasound assessment at the location of calcium within the arterial wall at the target site.…”
mentioning
confidence: 99%